CAFF Habitat Conservation Report No.9 - Gaps in Habitat Protection in the Russian Arctic - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (Conservation of Arctic Flora and Fauna Working Group (CAFF), 2000)
Arctic Council's CAFF Working Group's Habitat Conservation Report No.9 - Gaps in Habitat Protection in the Russian Arctic